Identification of Geothermal System In “Diana” Area, Indonesia Based On Magnetotelluric Data Modelling - Fajar Alpine; Y. Yatini; Iqbal Takodama (UIR PRESS, 2022)
These days, the number of geothermal explorations is being increased to obtain a greater new potential of geothermal energy. One of the methods that is often used is magnetotelluric (MT). By MT, the components of a geothermal system can be delineated based on the resistivity values. This research’s main purpose is MT data modelling in 1 D and 2 D to delineate the geothermal system in the research area. There are 18 point of soundings, with a distance of about 1 – 3 km for each point. Bostick Transformation is used in 1 D modelling while Non-Linear Conjugate Gradient inversion is used as 2 D modelling with L – curve analysis as a method to obtain an optimal value of regularization parameter. Based on the analysis of 1 and 2 D models, the caprock zone was identified with a resistivity value of < 50 Ωm at a depth of 500 m with a thickness of about 250 m. The reservoir zone was identified with a resistivity value range of (50 – 100) Ωm located at a depth of 1000 with a thickness of about 500 m. Also, fault structures have been identified at the center of the research area. The regularization parameter used for the 2 D modelling is 5, which has obtained RMS values of 2.25% and 2.21% for each line.